The Performance Of The Gravitas Act In The Architectural Products - Zahraa ahmed Aljbury; Abdullah Saadoon Salman Almaamouri (المجلة العراقية لهندسة العمارة والتخطيط, 2018)
The importance of the act of gravitas in architecture show as a normative rule on the sublimity and nobility of architectural products, through the characteristics of objective rationality and social interaction which is characterized by the act of gravitas such as clam, persistence, seriousness and others . Thus, a series of architectural studies and invitations have recently emerged to restore the gravitas of architectural product, having been overshadowed by the features of manipulation, ironic, softness, self-selectivity and other features that contradict the characteristics of the gravitas act. The studies implicitly or explicitly introduce a set of performance characteristics to achieve the act of gravitas in the architectural output, but did not refer to it as a special study and a comprehensive collection that can be referred to as a standard rule or design characteristics that benefit the designer in building his  architectural work (the research problem). The general objective of the research is consistent with the calls for a return to values in architectural products, and specifically seeks to find the characteristics of the performance of the act of gravitas in the architectural output to reach the most important mechanisms and formal elements. The research adopted a synthetic analytical approach between the supporting studies and the architectural studies to derive a comprehensive theoretical framework for the performance of the act of gravitas in architectural output. And then its application to test the hypotheses. The research found two fundamental aspects of the performance of the gravitas, a formal aspect, which was characterized by the repose of form and gravity of form, and an interactive aspect related to the characteristics of the form associated with human and society and represented the value commitment in form and strictness in form.